Revealing the Impact: Online Teaching Effectiveness and Student Outcomes during the COVID-19 Pandemic at the University of Cape Coast - Kenneth Kwesi Nyarko; Hayford Asare Obeng; Richard Arhinful (PT ARRUS Intelektual Indonesia, 2024)
This study uses the Technology Acceptance Model (TAM) as a theoretical framework to investigate the significant effects of online instruction during the COVID-19 epidemic at the University of Cape Coast. The main objective is to look into how the effectiveness of online learning environments affects crucial student outcomes like behaviour, engagement, technology assistance, and overall performance. The study utilised a quantitative cross-sectional design, and data collection methods included simple random sampling procedures. The study's primary focus was the unique environment of Ghana's University of Cape Coast. The Technology Acceptance Model led the inquiry, and SPSS was used for statistical analysis. The study's findings show that the efficiency of online learning environments has a significant and favourable impact on students' performance, behaviour, and technological support. This highlights the critical role that effective online instruction plays in influencing favourable student outcomes and laying the groundwork for well-informed decisions about instructional strategies. The study's application highlights the strategic value of funding efficient virtual education systems. Educational institutions can use these insights to enhance online instruction, make the most of technology support services, and fine-tune curriculum design to improve student outcomes.